Formalization of Workflows and Correctness Issues in the Presence of Concurrency - Arpinar, ÏsmaÏlcem Budak; Halici, UĞur; Arpinar, Sena; DoĞaÇ, Asuman (Distributed and parallel databases : an international journal, 1999)
An account is given on the concurrency control aspects of workflow systems. The fundamental issue of correctness criterion specific to workflow systems is defined through inter-activity constraints and basic constraints by using the semantic workflow information available at design-time. Based on this criterion, the Constraint Based Concurrency Control (CBCC) mechanism is defined. Another technique called the Constraint Locking Concurrency Control (CLCC) mechanism is also considered. Both techniques are easy to implement. Performance analysis reveals that the two techniques have better performance than an optimistic approach based on the constraints.